The Boston Women’s Educational and Industrial Union: When Business Undergirded Claims to Political Participation (1877-1920) - Jeanne Boiteux (Transatlantica)
This article is a case study of a Progressive Era women’s voluntary association, the Women’s Educational and Industrial Union of Boston. It is an examination of the ways in which some reform organizations headed and staffed by women could embrace and then flaunt a business ethos in order to increase their standing and authority, especially in the context of public–private partnerships. Before the Nineteenth Amendment, at a time of municipal reform, female reformers—even those who were not suffragists—used their shared social background with politicians in a show of gendered class interests. Using Derrick Spire’s framework of “performative citizenship,” we take a look at the way college-educated women constructed an economic and political identity as businesswomen.